CHARACTER ANALYSIS THROUGH DIALOGUE IN ENOLA HOLMES (2020): A STUDY USING M.H ABRAM’S THEORY - Aistyana, Tyas Putri; Prastiwi, Yeny (Universitas Islam Sumatera Utara (UISU), 2025)
This study examines the characterization of the film Enola Holmes (2020), focusing on the emotional, intellectual, and moral aspects of the characters as revealed through dialogue. By employing qualitative analysis, the research explores how character’s self-reliance, resilience, and rejection of social norms through dialogue. Using M.H. Abram’s theory of characterization and Schachter-Singer’s two-factor theory of emotion, the study provides a deeper understanding of how emotions, cognitive processes, and physiological reactions are intertwined in shaping the characters’ traits. While previous studies focused more on gender representation in films, this study fills the void by highlighting the role of dialog in shaping character identity. This study has found that dialog not only functions as an expositional tool, but also as a primary means to convey thematic depth and character complexity. This study contributes to the discourse of film analysis by showing how dialog serves as a narrative device that engages the audience and reinforces the portrayal of characters as multidimensional.